Effects of microbial agents on cadmium uptake in Solanum nigrum L. and rhizosphere microbial communities in cadmium-contaminated soil - You, Meng; Wang, Li; Zhou, Guopeng; Wang, Yikun; Wang, Kai; Zou, Rong; Cao, Weidong; Fan, Hongli (Frontiers in Microbiology, 2023)
Solanum nigrum L. and microbial agents are often used for the remediation of cadmium (Cd)-contaminated soil; however, no studies to date have examined the efficacy of using various microbial agents for enhancing the remediation efficiency of Cd-contaminated soil by S. nigrum. Here, we conducted greenhouse pot experiments to evaluate the efficacy of applying Bacillus megaterium (BM) along with citric acid (BM+CA), Glomus mosseae (BM+GM), and Piriformospora indica (BM+PI) on the ability of S. nigrum to remediate Cd-contaminated soil. The results showed that BM+GM significantly increased the Cd accumulation of each pot of S. nigrum by 104% compared with the control. Application of microbial agents changed the soil microbial communities, and activities of Catalase (CAT) and urease (UE), soil organic matter, available N and total Cd were the main influencing factors. By constructing the microbial co-occurrence networks, the soil microbe was divided into four main Modules. BM+GM and BM+PI significantly increased the relative abundance of Module 1 and Module 3, respectively, when compared with the control. Additionally, Module 1 showed a significant positive correlation with translocation factor (TF), which could be regarded as the key microbial taxa. Further research found that Ascomycota, Glomeromycota, Proteobacteria, and Actinobacteria within Module#1 were also significantly correlated with TF, and these key species enriched in BM+GM. Overall, our findings indicate that the BM+GM treatment was the most effective for the remediation of Cd pollution. This treatment might promote the ability of S. nigrum to remediate Cd-contaminated soil through its effects on the rhizosphere microbial community